Tactics of top-level competitors in cross-country skiing - Cepulenas, A. (Kinesiology, 2004)
The aim of the work is to analyze the characteristics of tactics of the top-level competitive skiers in long-distance ski racing. We have analyzed the competitive activity indices of the highly proficient male and female competitive skiers who participated in the Winter Olympics in Albertville, Lillehammer and Nagano, and in the World Skiing Championship in Trondheim (Norway) in 1997. The indices were as follows: average distance speed, changes in gliding speed over separate legs, and changes in placings after different legs. We have also examined the changes in the split times of covering the first and the second leg of a 30-km race. It has been determined that both male and female skiers who develop a higher speed in the middle of the race glide faster in the slower and faster intervals of their races in comparison to the skiers whose average distance speed is lower. The study has shown that the speed in the first 15-km leg of the 30-km race was lower than in the second lap of the race. The top-ten male competitive skiers in classical style covered the second leg of the distance with a2.90±1.37% poorer result in the 30-km race in the Albertville Olympics. The female top-ten competitive skiers in free style, covered the second leg of the race with a 2.97±2.14% poorer result in the 30-km race in the Lillehammer Olympics. The female top-ten skiers in classical style covered the second 15-km leg of the distance with a 2.79±1.30% poorer result in the 30-km race in the Lillehammer Olympics. The following variations of skiers' tactics were determined during the competitions: • The whole distance is pursued almost equally at individual optimal speeds and skiers try to keep to equal work intensity over the distance. • Some skiers lose insignificantly to rivals at the beginning of the race. In the middle of the distance they catch up with others, exceed the speed and finally win better places in competitions. This way of gaining a victory over the rivals proved to be wiser than the way in which skiers try to win better places at separate intervals of the first leg of the race. • The distance coverage is started at high speed. Skiers cover the first kilometers in a leading group. At this point the leaders win against the main rivals, but in the middle of the race and at the finish they are seldom able to keep their gained superiority. Nevertheless, they win high places, but lower than at the beginning of the race. • The beginning and the middle of the race are gained with high optimal speed; some skiers try to save some energy for the finish and to beat the competitors in the second leg of the race by powerfully gliding through last kilometres. These are strong finishing tactics. • Skiers with a higher average distance speed glide faster in both the slowest and the fastest intervals of the race than the skiers whose average distance speed is lower. Elite skiers, competing for medals and placed among the top six, take the leading positions in the first leg of the race and retain them till the end.